Understanding farmers’ indicators in climate-smart agriculture prioritization in the Southern Agricultural Growth Corridor of Tanzania (SAGCOT). - Shikuku, Kelvin Mashisia; Mwongera, Caroline; Winowiecki, Leigh Ann; Twyman, Jennifer; Läderach, Peter R.D. (International Center for Tropical Agriculture, 2016)
In order to increase the uptake of climate-smart agriculture (CSA) technologies, it is important to understand the contexts in which farmers operate. Farmers use different indicators to decide whether or not to implement, what to implement, and where to implement specific technologies. Identifying and understanding such indicators can be helpful to efforts aiming to scale out adoption. The purpose of this study was to identify indicators that farmers use to prioritize agricultural innovations, in general, and CSA, in particular.